2009
DOI: 10.1111/j.1443-1661.2009.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Prognosis of Bile Duct Stones: Endoscopic Papillary Balloon Dilatation Versus Endoscopic Sphincterotomy

Abstract: Low-pressure EPBD in combination with isosorbide dinitrate enabled preservation of papillary functions by 70%, which would improve a long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Bile duct stone recurrence rate after ES-LBD was 6.9%, which was similar to that of previous studies that evaluated ES-EPBD or EPBD alone 4,5,14. There was no significant difference in potential risk factors for bile duct stone recurrence between the ES alone and the ES-LBD group.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Bile duct stone recurrence rate after ES-LBD was 6.9%, which was similar to that of previous studies that evaluated ES-EPBD or EPBD alone 4,5,14. There was no significant difference in potential risk factors for bile duct stone recurrence between the ES alone and the ES-LBD group.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, these factors may prompt the use of ES-LBD for stone removal. Gallbladder stone is a known risk factor for bile duct stone recurrence 14,15. Cholecystectomy is usually recommended to prevent bile duct stone recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, EPBD results in less trauma to the ampullary sphincter. Second, EPBD might preserve the function of the biliary sphincter [2] , reducing late complications such as the recurrence of biliary stones [23,24] . Third, EPBD has the advantage of less bleeding and is safer for patients with bleeding tendency.…”
Section: Resultsmentioning
confidence: 99%
“…It is presumed that EPBD could preserve the sphincter function and reduce the occurrence of duodenobiliary reflux and bacteria contamination, thus decreasing the biliary stone recurrence. 10,12 A retrospective study by Kojima et al 12 revealed that the recurrence rate of CBD stones was higher in 233 patients after EST than in 453 patients after EPBD (17.0% vs. 6.8%, p < 0.05), and the sphincter of Oddi function was protected in 70% patients after EPBD. A meta-analysis also showed that the stone recurrence rate was significantly reduced in EPBD as compared with that in EST.…”
Section: Recurrence Rate Of Biliary Stones After Epbd/eplbd or Estmentioning
confidence: 95%